Apresentação do modelo de ensino aprendizagem Peer Instruction para ser aplicado na graduação em Odontologia - SANTOS, Priscila Carvalho dos (2019)
Considering the profile of the students nowadays, this paper presents a proposal to elaborate the evaluation of the teaching-learning process of the degree in Dentistry, using the active methodology called Peer Instruction (PI). The IP promotes a critical understanding of the subjects studied through the interactivity between the participants and the requirement to be co-responsible for successful learning. Associated with the use of technologies that allow access to the Internet, the methodology attracts students through agility in the tests, boosting interest. The proposed evaluation is related to the performance of learning process, as well as the perception of the students about the method. The evaluation model allows its application in any curricular element of the Dentistry Course.